Unveiling TWC replacement benefits in in-use vehicles from a concentration-reactivity-toxicity perspective - Jie Yao; Xinping Yang; Yongdong Wang; Jian Wang; Yanjun Wang; Chao Peng; Hongfei Chen; Xin Li; Yunjing Wang; Yan Ding (Environmental Pollution, 2026)

GeoMRF: A knowledge-enhanced recommendation framework for mitigating adverse geological conditions in railway tunnel construction - Qiyu Huang; Qing Zhu; Yulin Ding; Tingchen Wu; Hongyu Wang; Haoyu Wu; Qianqian Sun; Yanjun Wang (Tunnelling and Underground Space Technology, 2026)

NearStitch: Robust near-surface image stitching for phenotyping - Yu Wang; Shichao Jin; Jianling Tang; Ke Wang; Shan Xu; Yanjun Su; Qinghua Guo; Dong Jiang; Yanfeng Ding; Frédéric Baret (Computers and Electronics in Agriculture, 2026)

MEHP exposure disrupts the self-renewal and differentiation of GC-1 cells by up-regulating m6A levels, leading to reproductive damage in immature rats - Yanjun Ding; Xiazhu Zhou; Yifan Hong; Jing Chen; Haohui Tang; Binrong Sun; Chunlan Long; Lianju Shen; Shengde Wu; Yuexin Wei; Guanghui Wei (Toxicology, 2026)

Data-driven insights into real-world N2O emissions across conventional and hybrid vehicles: Transient impacts and driving factor identification - Huayang Zhao; Mingshen Ma; Zhou Yin; Han Jiang; Haiguang Zhao; Lei Zu; Yitu Lai; Yunjing Wang; Yanjun Wang; Hang Yin; Yan Ding (Journal of Hazardous Materials, 2026)

Chronic heat exposure induces brain atrophy in mice: Molecular signatures and AI-driven intervention strategy - Wenxin Xiang; Bo Yin; Qi Huang; Shisu Li; Miaohui Ding; Guoqing Feng; Ruoran Li; Dizhi Wang; Leizi Min; Xingyuan Hu; Limei Ke; Linfeng Liu; et al. (Journal of Environmental Sciences, 2026)

Migration and transformation pathways of Alkali/Alkaline earth metals and chlorine during co-gasification of biochar and Coal: An experimental and thermodynamic analysis - Qianqian Guo; Hongtao Liu; Yanjun Hu; Lu Ding; Long Jiao; Shuai Liu; Xu Wang; Lingqin Zhao; Fan Yu (Fuel, 2026)

Sophaline B inhibits non-small cell lung cancer by activating NLRP3/caspase-1/GSDMD-dependent pyroptosis and PI3K/AKT/mTOR-mediated autophagy - Yibo Hou; Zhongfu Wang; Yang Wu; Ting Deng; Siyu Yang; Shaohua Ma; Yubo Zhang; Ding Luo; Yanjun Chen; Xiaoyong Dai (Natural Product Research, 2026)

Trianglamine-based polyurea nanofiltration membranes with exceptional acid stability and high dye/salt selectivity - Langyu Chen; Dibao Zhu; Qisheng Miao; Sisi Li; Yixuan Luo; Shiyu Liu; Weihang Jiang; Yanjun Ding; Tiefan Huang (Chemical Engineering Journal, 2026)

Accumulation pattern, source apportionment and risk assessment of soil heavy metals across diverse land use types: Insights from the northern foothills of Qinling mountains, China - Bingyao Huo; Yanjun Shen; Yibing Ning; Wei Shen; Penghui Ma; Zhijie Jia; Luqing Zhao; Junyan Zhao; Xing Chen; Tao Ding; Sirui Li; Jianbing Peng (CATENA, 2026)

Non-Invasive functional assessment of severity in cerebral arterial stenosis using cerebral flow fraction: A hemodynamic study - Hao Sun; Bao Li; Zijie Wang; Liyuan Zhang; Jun Zhao; Yanping Zhang; Guangfei Li; Jinli Ding; Yanjun Gong; Hwa Liang Leo; Youjun Liu (Medical & Biological Engineering & Computing, 2026)

The temperature and multi-species evolution during the oxidation of CH3OH/NH3 blends behind reflected shock waves - Dao Zheng; Youquan Yang; Haoyu Tian; Zhimin Peng; Dong He; Yanjun Ding; Yanjun Du (Fuel, 2026)

Research on precursory warning of damage and failure in freeze-thaw sandstone based on acoustic-thermal joint monitoring - Hui Liu; Mengjie Liu; Gengshe Yang; Xinyue Dai; Yanjun Shen; Bo Liang; Xiao Ding; Yali Xu; Runqi Wang (Cold Regions Science and Technology, 2026)

N2O and NO formation and inhibition influenced by calcium (Ca) during coal char combustion - Zhi Han; Ping Liu; Yanjun Zuo; Yingchuan Zhou; Xiaoshuo Liu; Xunlei Ding; Jianming Xue; Yufeng Duan (Fuel, 2025)

Transparent analysis of compression damage propagation of freeze-thaw rock based on CT-DVC - Hui Liu; Mengjie Liu; Gengshe Yang; Yanjun Shen; Bo Liang; Xiao Ding; Xinyue Dai; Minkai Zhu; Runqi Wang (Cold Regions Science and Technology, 2025)

SenNet: A dual-branch image semantic segmentation network for wheat senescence evaluation and high-yielding variety screening - Jiaqi Yao; Shichao Jin; Jingrong Zang; Ruinan Zhang; Yu Wang; Yanjun Su; Qinghua Guo; Yanfeng Ding; Dong Jiang (Computers and Electronics in Agriculture, 2025)

Molecular fingerprints of dissolved organic matter leached from microplastics over prolonged photochemical aging: Implications for aquatic carbon cycling - Zekun Zhang; Zhao Liang Chen; Yanjun Liu; Yuanbi Yi; Ruanhong Cai; Ming Ye; Mengyang Liu; Meng Yan; Kenneth M.Y. Leung; Ding He (Water Research, 2025)

OSNet: an oriented instance segmentation network of breeding plot extraction from UAV RGB imagery - Ruinan Zhang; Yuanhao Zhang; Shichao Jin; Jingrong Zang; Ruofan Zhao; Jiaqi Yao; Shaochen Li; Qing Li; Yanjun Su; Jin Wu; Qinghua Guo; Yanfeng Ding; et al. (Computers and Electronics in Agriculture, 2025)

STANet-TLA: leveraging deep learning and prior knowledge for large-scale soybean breeding plot segmentation and high-yielding variety screening from UAV time-series data - Shaochen Li; Yinmeng Song; Ke Wang; Yiqiang Liu; Junhong Xian; Hongshan Wu; Xintong Zhang; Yanjun Su; Jin Wu; Qinghua Guo; Shan Xu; Dong Jiang; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Mechanism of action of pulsed electric field on lactoferrin: Functional properties, structure and aggregation behavior - Yuhui Ding; Hongfang Cao; Cheng Zhang; Yanjun Tong; Caiyun Wang; Jian He; Wei Zhao; Ruijin Yang (Food Chemistry, 2025)

Synergistic nano-bioeffects: Dual impact of bisphenol-derived carbon dots on environmental health and antimicrobial therapy - Siyuan Hu; Xinzhong Zhang; Jiayu Li; Xiang Wang; Chen Gao; Jiatong Zhou; Jing Cai; Miaomiao Yin; Rufang Zhao; Xin Ding; Wei Hong; Yanjun Hu (Chemical Engineering Journal, 2025)

Renewable bamboo-based composites for electromagnetic and thermal applications - Xiaolong Li; Haonan Ding; Yu Wang; Jinhai Guo; Yanjun Li; Tiancheng Yuan (Journal of Cleaner Production, 2025)

Insight into perfluorooctanoic acid-induced impairment of mouse embryo implantation via single-cell RNA-seq - Xiaoqiang Sheng; Yanjun Yang; Jiao Tian; Zhe Zhang; Lijun Ding; Junzhao Zhao (Journal of Hazardous Materials, 2025)

Study of the initiating and resisting mechanisms of toppling deformations in anti-inclined rock slopes - Yibing Ning; Huiming Tang; Jianbing Peng; Yanjun Shen; John V. Smith; Tao Ding (Bulletin of Engineering Geology and the Environment, 2025)

3D printing food flow in different extruders based on crazy and adaptive salp swarm algorithm-deep extreme learning machine improved-lattice Boltzmann method - Weiwei Wu; Minheng Gu; Xin Liu; Zhongyi Shan; Shuang Ding; Yanjun Zhang; Wenhan Yang (Journal of Food Engineering, 2025)

An Al2O3@ZnO membrane for oil-in-water emulsion separation with photocatalytic regeneration prepared via a simple deposition route - Chenggui Kuang; Yanjun Li; Donghua Liu; Yongfeng Li; Daofeng Sun; Jin Chen; Donghai Ding; Guoqing Xiao (Journal of Water Process Engineering, 2024)

Induction of brand new Na3 sites constructing high performance Na3V2(PO4)3 with low strain property and high thermal safety - Yuru Zhao; Changcheng Liu; Que Huang; Hongyuan Ding; Jianghui Xie; Baofeng Zhang; Yanjun Chen (Chemical Engineering Journal, 2024)

Critical analysis of using recycled wax oils in asphalt binder considering exudation effects - Han Liu; Bo Su; Haibo Ding; Yanjun Qiu (Fuel, 2024)

Characterization of wax precipitation in wax-doped asphalt binders by variable-temperature polarized light microscope and improved viscosity algorithm - Hai Yuan; Junhao Liu; Bo Su; Jianmin Ma; Haibo Ding; Yanjun Qiu (Fuel, 2024)

Effects of dietary glycerol monolaurate on growth and digestive performance, lipid metabolism, immune defense and gut microbiota of shrimp (Penaeus vannamei) - Renzhi Liu; Yanjun Ding; Futao Jing; Zhifei Chen; Chen Su; Luqing Pan (Fish & Shellfish Immunology, 2024)

A Pickering emulsion stabilized by Chitosan-g-Poly(N-vinylcaprolactam) microgels: Interface formation, stability and stimuli-responsiveness - Yue Li; Mengting Chen; Yanjun Ding; Yanke Li; Mingming Guo; Yichuan Zhang (Carbohydrate Polymers, 2024)

Regulation of interfacial polymerization by organic base for high-permselective nanofiltration - Huiying Ding; Yuting Liu; Zhong Zhang; Yanjun Cheng; Jiahao Mo; Lu Elfa Peng; Cheng Xiang; Hongchang Pei; Xianhui Li (Desalination, 2024)

Investigation of the NH3 consumption and H2O/NO formation during the oxidation of n-heptane and iso-octane blended with ammonia - Dao Zheng; Zhimin Peng; Dong He; Meng Zhang; Jidong Li; Yanjun Ding; Yanjun Du (Fuel, 2024)

Mid-infrared absorption spectroscopy measurements and model improvements during the oxidation of ammonia/ethanol and ammonia/diethyl ether blends in a shock tube - Dao Zheng; Dong He; Yanjun Du; Meng Zhang; Jidong Li; Yanjun Ding; Zhimin Peng (Fuel, 2024)

ESE-1 mediates lipopolysaccharide-induced BV2 cell inflammation via upregulation of HMGB1 expression - Yaojun Lu; Juan Ding; Jiaojiao Huang; Yanjun Zhao (Journal of Biosciences, 2023)

Ammonia emission characteristics and ammonia injection control from stationary source in flue gas denitrification system - Zhiping Wang; Chengyi Sun; Aijun Shi; Jing Yan; Lei Nie; Lei Chen; Peili Zhou; Yanjun Ding; Yong Yang; Xianglong Jing (Journal of Cleaner Production, 2023)

Solubility and structural parameters of asphaltene subfractions separated from bitumen via an improved method - Hai Yuan; Azuo Nili; Jiale Chen; Haibo Ding; Han Liu; Yanjun Qiu (Fuel, 2023)

Enlarged fins of Tibetan catfish provide new evidence of adaptation to high plateau - Liandong Yang; Ning Sun; Honghui Zeng; Ying Wang; Wenjun Chen; Zufa Ding; Yang Liu; Jing Wang; Minghui Meng; Yanjun Shen; Jingliang Kang; Xiuhui Ma; et al. (Science China Life Sciences, 2023)

Ultrafast loose nanofiltration membrane intercalated by in-situ grown nanoparticles for dye purification and reuse - Yuting Liu; Jiahao Mo; Huiying Ding; Yanjun Cheng; Zhong Zhang; Chen Wang; Xianhui Li (Desalination, 2023)

Analysis of Water Resonance in the Inner Domain of a Large Fixed Floating Tourist Platform Based on a 3D Non-Hydrostatic Model - Zhiqiang Liu; Yanjun Mao; Jun Ding; Chao Tian; Siyu Wang; Congfang Ai; Xiaozhou Ma; Guohai Dong (Journal of Marine Science and Engineering, 2023)
In order to meet the needs of marine tourism development, this paper analyzes the water resonance in the inner domain of a fixed floating tourist platform based on a 3D non-hydrostatic model. The tourist platform has a complex structure that is prone to the resonance of the water in the inner domain under wave actions. The water’s motion response in the platform’s inner domain under wave action is simulated numerically using numerical simulation methods. The non-hydrostatic model used in this paper is based on a semi-implicit method to solve the incompressible Navier–Stokes equations (NSE) and combines the immersed boundary method with the global continuity equations in the pressure zone (the flow zone under the structure) to approach the problem. In this paper, firstly, the resonant frequencies and resonant amplitudes of the water inside the box-shaped ship are calculated and compared with the experimental data to demonstrate the non-hydrostatic model’s accuracy in calculating the resonance problem of the water in the inner domain of a fixed floating platform. Secondly, the water’s resonant frequencies and resonant modes in the inner domain are calculated by numerical modeling of the floating tourist platform, including rare high-order resonance modes. We found that there are six resonance modes with complex shapes in the water of the inner domain of the tourist platform. Furthermore, the effects of the wall thickness, chord distance and draft of the annular tourist platform on the resonant amplitude values and modes of the water domain within the platform are analyzed in depth.

Study of effects of dietary quercetin (Que) on growth performance and disease resistance mechanism of Litopenaeus vannamei - Zhifei Chen; Depeng Fan; Luqing Pan; Chen Su; Yanjun Ding; Mingxiang Lu (Aquaculture, 2023)

Dietary cholesterol enhances osmoregulation, antioxidant defenses and immune response of Litopenaeus vannamei to alleviate the macromolecular damage induced by salinity stress - Chen Su; Jinbao Li; Mengyu Zhang; Luqing Pan; Yuxuan Wang; Yanjun Ding; Zhifei Chen; Mingxiang Lu (Aquaculture, 2023)

Review on recent progress in on-line monitoring technology for atmospheric pollution source emissions in China - Huanqin Wang; Jitong Zhou; Xue Li; Qiang Ling; Hongyuan Wei; Lei Gao; Ying He; Ming Zhu; Xiao Xiao; Youjiang Liu; Shan Li; Chilai Chen; et al. (Journal of Environmental Sciences, 2023)

Spatially resolved broadband absorption spectroscopy measurements of temperature and multiple species (NH, OH, NO, and NH 3 ) in atmospheric-pressure premixed ammonia/methane/air flames - Xinyu Yang; Zhimin Peng; Yanjun Ding; Yanjun Du (Fuel, 2023)

Immunodominant membrane protein (Imp) promotes the transmission of wheat blue dwarf (WBD) phytoplasma by directly interacting with α-tubulin in leafhoppers - Lei Ding; Wenjing Lu; Yanjun Yang; Qinrong Zhong; Tong Zhou; Guiling Wang; Chengyan Song; Wendong Ma; Wei Chen; Yunfeng Wu (European Journal of Plant Pathology, 2022)

Mooring Stability Study for Novel Wave Energy Converter Based on Regular Wave - Zhongliang Meng; Yun Chen; Yanjun Liu; Yi Ding (Journal of Marine Science and Engineering, 2021)
The mooring system not only plays a vital role in keeping wave energy generators floating stably, but also affects the success of engineering design. Combining wave force theory and the hydrological data obtained from the field measurements of a certain sea area in the Bohai Sea, the Stokes second-order wave theory was adopted to design the mooring system of a new type of power-generating device. At the same time, the study uses the Aqwa software to gather the dynamic data of a power-generating device in a real test, and then makes models and carries out regular wave tests so as to verify the viability of the mooring system and the stability of the whole power-generating device. All of this work will provide a theoretical basis for the manufacture of an engineering prototype and its reliable supply of power.

Identification of hub lncRNA ceRNAs in multiple sclerosis based on ceRNA mechanisms - Yanjun Ding; Taotao Li; Xinwei Yan; Mintian Cui; Chao Wang; Situo Wang; Fengmin Zhang; Ruijie Zhang (Molecular Genetics and Genomics, 2021)

Design of Full-Ocean-Depth Self-Floating Sampler and Analysis of Factors Affecting Core Penetration Depth - Yugang Ren; Yanjun Liu; Zhongjun Ding; Baohua Liu; Jianhua Zhang (Journal of Ocean University of China, 2020)

Origin and depositional paleoenvironment of Triassic polyhalite in the Jialingjiang Formation, Sichuan Basin - Yanjun Zhao; Chenglin Liu; Ting Ding; Luis A. Gonzalez; Zhaoqi Li; Mingquan Wang; Licheng Wang; Zhengjie Zhu (Carbonates and Evaporites, 2020)

Chlorine isotope analysis of Triassic salt rock and geological significance of ancient salt lake in Sichuan Basin, China - Ting Ding; Chenglin Liu; Yanjun Zhao; Zhengjie Zhu (Carbonates and Evaporites, 2019)

Transplantation of umbilical cord–derived mesenchymal stem cells on a collagen scaffold improves ovarian function in a premature ovarian failure model of mice - Yanjun Yang; Lei Lei; Shanshan Wang; Xiaoqiang Sheng; Guijun Yan; Lu Xu; Jingyu Liu; Mengyuan Liu; Xin Zhen; Lijun Ding; Haixiang Sun (In Vitro Cellular & Developmental Biology - Animal, 2019)

Transplantation of UC-MSCs on collagen scaffold activates follicles in dormant ovaries of POF patients with long history of infertility - Lijun Ding; Guijun Yan; Bin Wang; Lu Xu; Yan Gu; Tong Ru; Xiaoying Cui; Lei Lei; Jingyu Liu; Xiaoqiang Sheng; Bin Wang; Chunxue Zhang; et al. (Science China Life Sciences, 2018)

Two ultraviolet radiation datasets that cover China - Hui Liu; Bo Hu; Yuesi Wang; Guangren Liu; Liqin Tang; Dongsheng Ji; Yongfei Bai; Weikai Bao; Xin Chen; Yunming Chen; Weixin Ding; Xiaozeng Han; et al. (Advances in Atmospheric Sciences, 2017)

The strong El Niño of 2015/16 and its dominant impacts on global and China's climate - Panmao Zhai; Rong Yu; Yanjun Guo; Qingxiang Li; Xuejuan Ren; Yaqiang Wang; Wenhui Xu; Yanju Liu; Yihui Ding (Journal of Meteorological Research, 2016)

Impacts of reference time series on the homogenization of radiosonde temperature - Yanjun Guo; Yihui Ding (Advances in Atmospheric Sciences, 2011)

Radiosonde temperature trends and their uncertainties over eastern China - Yanjun Guo; Peter. W. Thorne; Mark P. McCarthy; Holly A. Titchner; Binxun Huang; Panmao Zhai; Yihui Ding (International Journal of Climatology, 2008)
Trends and uncertainty in radiosonde temperature records for six sample stations in eastern China are assessed. Results from a complex approach using metadata and a two‐phase regression (M‐TPR) to capture known and unknown metadata events respectively are compared with an ensemble of possible solutions generated by the Met Office automated homogenization system (QUARC). Independent satellite records from the Microwave Sounding Unit (MSU) record are used to validate breakpoints over the satellite era. Differences in the treatment of metadata and the strictness of the statistical breakpoint detection methods used lead to relatively poor agreement in breakpoint identification. Agreement in long‐term (1958–2003) trends in the homogenized data was found to result from a fortuitous cancellation of large differences in the pre‐ and post‐satellite era trends between the two approaches. A consideration of independent MSU satellite data lends some credence to the presence and calculated magnitude of many of the assigned breakpoints that were not associated with recorded metadata events, in the later part of the record. However, it also highlights that neither of the approaches is likely to be perfect at identifying breaks. Improved metadata are likely to prove vital in confirming the presence of these breaks and hence the veracity of the various homogenization approaches to data for eastern China. Copyright © 2007 Royal Meteorological Society